Morphometric characteristics of changes in the anterior abdominal wall muscles after implantation of polypropylene meshes of different types in experiment - Piatnochka, V. I. (Journal of Education, Health and Sport, 2018)
A widespread introduction of modern alloplastic materials into the surgical practice has significantly improved the results of surgical treatment of the patients with ventral and postoperative ventral hernia. However, the implantation of synthetic material into the anterior abdominal wall tissues is accompanied by different local reactions, especially when using ‘heavyweight’ meshes that often cause development of complications. The analysis of the results determines the topical issue of this study. Objective. The aim of the study was to conduct a morphometric evaluation of changes in the anterior abdominal wall muscles after the implantation of ‘heavy’ and ‘light’ polypropylene meshes as well as ‘light’ ones in combination with the PRF membrane. Materials and methods. Morphometric study involved analysis of anterior abdominal wall muscles after implantation of ‘heavy’, ‘light’ polypropylene meshes, as well as the ‘light’ ones in combination with the PRF membrane, into the retro-muscular space in light-optical investigation of microslides. The experiments were carried out on 18 mature male Vietnamese pigs, which were divided into 6 groups. Results. In the group of animals 2m significant structural changes of muscles were revealed. The diameter of myocytes increased from (13.50±0.15) to (14.20±0.18) µm. These morphometric parameters statistically significantly (p<0.05) differed among themselves. In this case, the last morphometric parameter exceeded the previous one by 5.2%. The diameter of nuclei of these structures changed more or less similarly. Thus, the diameter of myocytes in the control group of animals was (5.10±0.04), and in the modeled experimental conditions it was (5.68 ± 0.06) μm. The relative volume of stroma in the muscles in the study groups with a high degree of statistical significance (p<0.001) increased by 16.6%. Herewith, stromal-myocyte ratio significantly changed. Thus, in the control group this morphometric parameter reached (0.168±0.003), and in the 2nd group of animals – (0.202±0.006). The quantitative morphometric parameters of anterior abdominal muscles in the experimental animals of the 5th group (3m) proved that they changed significantly in response to the experiment; thus, in this case the diameter of myocytes statistically significantly increased from (13.50±0.15) µm to (14.10±0.15) μm, i.e. by 4.4%. The diameter of the studied cells in the modeled experimental conditions statistically significantly (p<0.001) increased from (5.10±0.04) to (5.60±0.05) μm. The last morphometric parameter exceeded the previous one by 9.8%. Conclusions. The quantitative analysis of morphometric evaluations of changes in the muscular layer of anterior abdominal wall, in cases of implantation of the polypropylene meshes of different types, in the late period of the experiment proved that during the implantation of the ‘light’ mesh, in this period of the experiment, the structural changes of anterior abdominal wall muscles were the least; and the most favorable features of structural changes of anterior abdominal wall were in the experimental animals, where a ‘light’ polypropylene mesh in combination with the PRF membrane was used for its plastics.